2021
DOI: 10.1021/acs.nanolett.1c03110
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Reversible Fluorescent Probe for in Situ Imaging of Extracellular Vesicles and Their Secretion from Living Cells

Abstract: Our knowledge in how extracellular vesicles (EVs) are secreted from cells remains inadequate due to the limited technologies available for visualizing them in situ. We report a pH-reversible boron dipyrromethene (BODIPY) fluorescent probe for confocal imaging of EVs secreted from living cells without inducing severe cytotoxicity. This probe predominantly assumes a non-fluorescent leuco-BODIPY form under basic conditions, but it gradually switches to its fluorescent parent BODIPY form upon acidification; such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…While these TEM imaging data suggest NP exocytosis, we acknowledge that TEM imaging can only capture still images of fixed cells and may not allow us to conclusively distinguish between endocytosis and exocytosis based on the direction of NP movement. Yet, live imaging of the exocytosis of a single NP and tracking its three-dimensional (3D) movement in culture medium remain challenging . The fluorescently labeled NPs, once released to the extracellular space, become significantly diluted by the culture medium; the low signal-to-noise ratio renders confocal imaging of the exocytosed NPs impractical (see SI Extended Results and Discussion).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these TEM imaging data suggest NP exocytosis, we acknowledge that TEM imaging can only capture still images of fixed cells and may not allow us to conclusively distinguish between endocytosis and exocytosis based on the direction of NP movement. Yet, live imaging of the exocytosis of a single NP and tracking its three-dimensional (3D) movement in culture medium remain challenging . The fluorescently labeled NPs, once released to the extracellular space, become significantly diluted by the culture medium; the low signal-to-noise ratio renders confocal imaging of the exocytosed NPs impractical (see SI Extended Results and Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, live imaging of the exocytosis of a single NP and tracking its three-dimensional (3D) movement in culture medium remain challenging. 33 The fluorescently labeled NPs, once released to the extracellular space, become significantly diluted by the culture medium; the low signal-to-noise ratio renders confocal imaging of the exocytosed NPs impractical (see SI Extended Results and Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…In response to various types of stimulation MVBs move, approaching the plasma membrane ( Figure 1 ) ( Calvo and Izquierdo, 2020 ). Understanding of these processes has been strengthened by the use of optical reporters associated with ILV markers ( Verweij et al, 2018 ; Liu X.-M. et al, 2021 ). Upon tethering to specific sites ( Davis et al, 2021 ), some heterogeneity in the molecules participating in MVB exocytosis has been reported among various cell types.…”
Section: Development Of Secretory Vesicles Within the Cellmentioning
confidence: 99%
“…Fluorescent proteins of exosome membranes, such as CD63-pHfluorin, start emitting fluorescence upon exocytosis. The steps revealed by these approaches are numerous, from the efficacy and intracellular signaling of exogenous stimuli to the frequency, localization and machinery of exocytosis, up to the navigation of the released vesicles ( Liu X.-M. et al, 2021 ; Gurung et al, 2021 ). The exosome localization studies have revealed various unexpected results.…”
Section: Development Of Secretory Vesicles Within the Cellmentioning
confidence: 99%
“…Fluorescent probes have been widely investigated for pH detection in vitro , in vivo , and in situ . So far, various fluorescent probes, such as organic fluorescent molecules, fluorescent polymers, fluorescent hydrogels, metal–organic framework materials, and quantum dots, have been designed with downshifted emissions as signals under ultraviolet light excitation, which, however, limits their applications with regard to physiological pH detection. In addition, the shortcomings of autofluorescence interference in organisms, poor penetrability of an ultraviolet (UV) excitation light source, and detection inaccuracies caused by concentration fluctuations of probe molecules cannot be ignored. …”
mentioning
confidence: 99%